Tutors Perception on a Training Workshop on Simulation Based Medical Education - Salam, Abdus; Saiboon, Ismail Mohd.; Jaafar, Mohd Johar; Hamzah, Faizal Amri; Balakrishnian, Balakrishnian; Kamarudin, Mohammad Arif; Yaman, Mohamad Nurman; Bujang, Siti Mariam; Siraz, Harlina Halizah (Bangladesh Journal of Medical Science, 2016)
Background: The notion of learning by doing has become less acceptable especially when invasive procedures are needed. Simulation provides learners the opportunity for deliberate practice. Universiti Kebangsaan Malaysia Medical Centre (UKMMC) is one of the promoter of Simulation-based medical education (SBME), conducting regularly train the trainer workshop aimed to increase the efficiency of learner. The objective of this paper is to provide an insight from the learners perspective on a SBME workshop. Methods: It was a pre and post-test design survey, done on a total of 21 participants of UKMMC who attended a 2-day train-the-trainer workshop on SBME held in April 2014 at Simulation Lab of Emergency Department. Participants were exposed to interactive-lectures, hands-on with scenario design-development using high fidelity simulator and trying out the scenario with simulation. Each simulation session lasted around 30 minutes, followed by a 15-minute debriefing and 10-minute didactic session. During debriefing, video clips of what participants did were shown. Participants completed pre-post evaluation on their pre-experience, usefulness of SBME and as feedback-method, and meeting the objectives of SBME-workshop. Results: Post-test evaluation showed 100% participants reported simulation was very useful compared to 43% in the pre-test. While 83% agreed feedback was better served by video-re-run in post-test compared to 43% in the pre-test. Most expressed that the workshop achieved the desired objectives. Conclusion: The SBME is an effective method to gain medical-procedural experience and is well accepted by the participants. Medical schools should use simulation as an educational tool in order to increase the efficiency of learners. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.195-200